Antagonistic Properties of Some Halophilic Thermoactinomycetes Isolated from Superficial Sediment of a Solar Saltern and Production of Cyclic Antimicrobial Peptides by the Novel Isolate Paludifilum halophilum. (27th July 2017) - Frikha Dammak, Donyez; Zarai, Ziad; Najah, Soumaya; Abdennabi, Rayed; Belbahri, Lassaad; Rateb, Mostafa E.; Mejdoub, Hafedh; Maalej, Sami
Abstract : This study has focused on the isolation of twenty-three halophilic actinomycetes from two ponds of different salinity and the evaluation of their ability to exert an antimicrobial activity against both their competitors and several other pathogens. From the 23 isolates, 18 strains showed antagonistic activity, while 19 showed activities against one or more of the seven pathogen strains tested. Six strains exhibited consistent antibacterial activity against Gram-negative and Gram-positive pathogens characterized at the physiological and molecular levels. These strains shared only 94-95% 16S rRNA sequence identity with the closely related species of the Thermoactinomycetaceae family. Among them, the potent strain SMBg3 was further characterized and assigned to a new genus in the family for which the name Paludifilum halophilum (DSM 102817 T ) is proposed. Sequential extraction of the antimicrobial compounds with ethyl acetate revealed that the crude extract from SMBg3 strain had inhibitory effect on the growth of the plant pathogen Agrobacterium tumefaciens and the human pathogens Staphylococcus aureus, Salmonella enterica, Escherichia coli, and Pseudomonas aeruginosa . Based on the HRESI-MS spectral data, the cyclic lipopeptide Gramicidin S and four cyclic dipeptides (CDPs) named cyclo(L-4-OH-Pro-L-Leu), cyclo(L-Tyr-L-Pro), cyclo(L-Phe-L-Pro), and cyclo(L-Leu-L-Pro) were detected in the fermentation broth of Paludifilum halophilum . To our knowledge, this is the first report on the isolation of these compounds from members of the Thermoactinomycetaceae family.